General Lexical Problems of Translation - Rasulova Zulfiya Kholmurotovna; Mirzakulov Uktamzhon Almardanovich; Rasulova Shakhnoza Iskandarovna (Research Parks Publishers, 2021)
Language is the main way of communication between people, and it is great if they speak the same language, but what if communication becomes impossible when the interlocutors speak different languages? Translation skills come to our aid here. The importance of translation and its special place in people's lives is becoming increasingly clear. Thanks to translation, people who speak different languages can communicate in multi-ethnic countries, translation provides cross-language and cross-cultural communication, and various teachings and religions are spread through translation. During the translation process, the specialist must pay attention to many factors that affect the adequacy and correctness of the translation.